Roles of Neutrophils in Glioma and Brain Metastases - Lin, Ya-Jui; Wei, Kuo-Chen; Chen, Pin-Yuan; Lim, Michael; Hwang, Tsong-Long (Frontiers in Immunology, 2021)
Neutrophils, which are the most abundant circulating leukocytes in humans, are the first line of defense against bacterial and fungal infections. Recent studies have reported the role and importance of neutrophils in cancers. Glioma and brain metastases are the most common malignant tumors of the brain. The tumor microenvironment in the brain is complex and unique owing to the brain-blood barrier or brain-tumor barrier, which may prevent drug penetration and decrease the efficacy of immunotherapy. However, there are limited studies on the correlation between brain cancer and neutrophils. This review discusses the origin and functions of neutrophils. Additionally, the current knowledge on the correlation between neutrophil-to-lymphocyte ratio and prognosis of glioma and brain metastases has been summarized. Furthermore, the implications of tumor-associated neutrophil phenotypes and the functions of tumor-associated neutrophils have been discussed. Finally, the potential effects of various treatments on tumor- associated neutrophils and the ability of neutrophils to function as a nano-carrier of drugs to the brain TME have been summarized. However, further studies are needed to elucidate the complex interactions between neutrophils, other immune cells, and brain tumor cells.